2020
DOI: 10.1262/jrd.2019-072
|View full text |Cite
|
Sign up to set email alerts
|

Season does not have a deleterious effect on proportions of stallion seminal plasma proteins

Abstract: The mechanism by which the content of the major groups of seminal plasma proteins in stallion semen changes between the breeding and non-breeding seasons remains unknown. Here, we investigated the proportions of non-heparin-binding, phosphorylcholine-binding, and heparin-binding proteins in seminal plasma with the aim of relating them to sperm quality and testosterone levels in good and bad freezer stallions. Only minor variations in the major protein groups were found between the breeding and non-breeding sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Other studies revealed lower DNA fragmentation and low intracellular calcium level, and higher total motility, viability (Wach‐Gygax et al., 2017) and progressive motility in the non‐breeding season (Greiser et al., 2020). Other studies found no differences between seasons in sperm quality (kinetic, morphological and functional parameters), testosterone concentrations or concentration of seminal plasma proteins in stallion semen (Blottner, Warnke, Tuchscherer, Heinen, & Torner, 2001; Johannisson et al., 2020; Warnke et al., 2003).…”
Section: Introductionmentioning
confidence: 92%
“…Other studies revealed lower DNA fragmentation and low intracellular calcium level, and higher total motility, viability (Wach‐Gygax et al., 2017) and progressive motility in the non‐breeding season (Greiser et al., 2020). Other studies found no differences between seasons in sperm quality (kinetic, morphological and functional parameters), testosterone concentrations or concentration of seminal plasma proteins in stallion semen (Blottner, Warnke, Tuchscherer, Heinen, & Torner, 2001; Johannisson et al., 2020; Warnke et al., 2003).…”
Section: Introductionmentioning
confidence: 92%
“…Morte et al 8 reported differences in spermatic concentration, vitality and morphology, but the progressive motility did not differ among seasons. Recently, Ebel et al 9 evaluated seasonal changes in the quality of sperm from fertile stallions, and only viability showed higher values during the breeding season; Johannisson et al 10 found minor variations in kinematics and morphology of sperm among seasons.…”
Section: Introductionmentioning
confidence: 99%
“…Seminal plasma proteins and factors surrounding them have been studied in different mammals, especially bulls 13 15 and stallions 16 18 . Such proteins are involved in important stages of fertilisation, such as the establishment of sperm reserves in the oviduct, capacity modulation and interaction between gametes 10 , 16 . Identifying, characterising and quantifying seminal plasma proteins therefore allow inferences about the animal reproductive status.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation